The Effect of Workload and Job Satisfaction on Outsourced Employee Performance - Qhisbullah, Ahmad; Mohyi, Achmad; Hilmi, Luqman Dzul (Jurnal Manajemen Bisnis dan Kewirausahaan, 2023)
The purpose of this study is to determine the effect of workload and job satisfaction on the performance of outsourced employees at PT Tema Wadah Lestari, Malang Regency partially and simultaneously. The research conducted is research using quantitative methods. The research population was 75 employees at PT Tema Wadah Lestari, Malang Regency. Sample determination using the saturated sample method so that the entire population was used as a research sample of 75 respondents. The data collection technique used by researchers is questionnaires. The data analysis method used is multiple linear regression using the SPSS program. The results of the study proved that workload has a significant effect on outsourced employee performance and job satisfaction has a significant effect on outsourced employee performance. The results of the study simultaneously (together) proved that workload and job satisfaction had a significant effect on the performance of outsourced employees at PT Tema Wadah Lestari, Malang Regency.